A Descriptive Study on Teachers’ Instructions in Teaching English During Covid-19 Pandemic At Islamic Elementary School - Inayah, Arin; Dimas Priagung Banar Syahputra (MAN Insan Cendekia Jambi, 2024)
Teaching English in Elementary school is hard. It is because there is no special English teacher whose scientific field is English. The students are taught by the classroom teacher. Furthermore, the facilities and environment in the process of teaching English is limited. To understand the elementary students in teaching and learning English, the teachers must be more creative and fun in giving material and make comfortable classroom. Before teaching, the teacher should prepare all needed in teaching and learning process, especially instructional giving to the students. This study aims to describe about the teachers’ instruction in teaching English during the Era of Covid-19 Pandemic at Islamic Elementary School of Tarbiyatus Sibyan, Srono-Banyuwangi. This study is descriptive qualitative research design which is describing the teaching and learning process about how the teachers are giving instruction in teaching English during Covid-19 pandemic. During the classroom activities, the teachers give clear instruction. After giving the instruction, the teachers ensure all students notice and understand all instruction given by the teachers. The teachers use suitable time in delivering the material. By choosing suitable time, the teachers can easy in delivering the material. When giving the instructions, the teachers give clear instructions by using easy language to be understood by the students. After giving the instruction, the teachers check the students understanding by giving feedback in the form of instruction given.